Characterisation and stability of anthocyanins in purple-fleshed sweet potato P40. (1st November 2015) - Xu, Jianteng; Su, Xiaoyu; Lim, Soyoung; Griffin, Jason; Carey, Edward; Katz, Benjamin; Tomich, John; Smith, J. Scott; Wang, Weiqun
Highlights: To identify anthocyanins in sweet potato P40 and assess stability during cooking. Total 12 acylated anthocyanins with more cyanidin than peonidin are identified. Anthocyanins are significantly reduced after cooking except for baking. Mono-acylated showed higher resistance against heat than di- and non-acylated. Acylated and cyanidin-predominated anthocyanins may offer extra health benefits. Abstract: Purple-fleshed sweet potato P40 has been shown to prevent colorectal cancer in a murine model. This study is to identify anthocyanins by using HPLC/MS–MS and assess the stability during various cooking conditions. P40 possesses a high content of anthocyanins up to 14 mg/g dry matter. Total 12 acylated anthocyanins are identified. Top three anthocyanins, e.g., cyanidin 3-caffeoyl-p-hydroxybenzoyl sophoroside-5-glucoside, peonidin 3-caffeoyl sophoroside-5-glucoside, and cyanidin 3-(6″-caffeoyl-6″-feruloylsophoroside)-5-glucoside, account for half of the anthocyanin contents. Over 80% of anthocyanins measured by acid hydrolysis were cyanidin derivatives, indicating P40 is unique when compared with other purple-fleshed sweet potatoes that usually contain more peonidin than cyanidin. Steaming, pressure cooking, microwaving, and frying but not baking significantly reduced 8–16% of total anthocyanin contents. Mono-acylated anthocyanins showed a higher resistance against heat than di- and non-acylated. Among of which, cyanidin 3-p-hydroxybenzoylsophoroside-5-glucoside exhibited the best thermal stability. The stable acylated and cyanidin-predominated anthocyanins in P40 may provide extra benefits for cancer prevention.